West African Economic and Monetary Union (WAEMU) : Staff Report on Common Policies for Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The staff report on discussions with regional institutions of the West African Economic and Monetary Union is presented. The region faced a number of challenges in 2011, with the intensification of the political crisis in Cote d'Ivoire and a large increase in global food and fuel prices. A materialization of downside risks could require a monetary policy relaxation for the union and differentiated fiscal responses across member countries. The drought in the Sahel may also require a more active fiscal policy in the affected countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet